(untitled) (Hoboken, NJ, 2004)
The book covers cognitive interviewing, interaction analysis, response latency, respondent debriefings, vignette analysis, split-sample comparisons, statistical modeling, mode of administration, and special populations. It also considers these topics in light of emerging techniques and technologies. The book's authors include more than two-dozen eminent professionals in a variety of fields related to survey methodology and questionnaire development, including names such as Gordon Willis of the National Cancer Insitute; Paul Beatty of the National Center for Health Statistics; Paul Biemerof the Research Triangle Institute; Don Dillman of the University of Washington; and Natacha Borgers, Edith de Leuuw, and Astrid Smits of Statistics Netherlands. Copious tables, figures, and references, as well as an extensive glossary, supplement the high quality discussion throughout the text
Keywords: Social surveys,Social sciences,Questionnaires,Phiếu điều tra,Khảo sát xã hội học,Khoa học xã hội; Methodology,Research,Methodology,Methodology,Phương pháp luận,Phương pháp luận,Nghiên cứu,Phương pháp luận